Pendekatan Repetitif melalui Hafalan Kitab Muḥāwarah untuk Meningkatkan Kepercayaan Diri Berbicara Bahasa Arab - Segaf Baharun (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2025)
In this era of globalization and increasing access to information, Arabic has become not only an essential medium for religious expression but also a bridge for intercultural communication. However, field observations reveal that many students still struggle with hesitation and anxiety when speaking, largely due to a lack of supportive linguistic environments and the pressure to achieve linguistic perfection. This situation raises a critical question regarding the effectiveness of current teaching methods and calls for innovative approaches that prioritize psycholinguistic factors. This study aims to examine the effectiveness of a repetitive approach through the memorization of the Muḥāwarah Book in enhancing the speaking confidence of students in Arabic. Speaking skills (maharah kalām) often pose a major challenge for learners, primarily due to doubt, anxiety, and limited language environments. Through systematic repetition of dialogues, students are expected to internalize sentence patterns automatically while cultivating a sense of security in communication. This qualitative descriptive study was conducted at Pondok Pesantren Darullughah Wadda’wah, Bangil, involving 120 new students. Data were collected through interviews, observations, and documentation, and analyzed thematically. The findings indicate that the structured repetition of muḥāwarah dialogues significantly improves oral participation, reduces anxiety, and strengthens students’ psychological readiness to speak. Repetitive memorization also produces a snowball effect by enhancing spontaneity, vocabulary acquisition, and fluency. This study underscores that learning Arabic requires not only linguistic strategies but also psycholinguistic approaches that build learners’ confidence.